Diabesity-associated oxidative and inflammatory stress signalling in the early human placenta. (April 2019) - Hoch, Denise; Gauster, Martin; Hauguel-de Mouzon, Sylvie; Desoye, Gernot
Abstract: Early pregnancy is characterized by a series of complex and tightly regulated events to ultimately establish implantation and early placental development. One of the key events is the opening of the decidual spiral arteries into the intervillous space. It leads to a rise in oxygen tension in the intervillous space and the placenta and will induce transcriptional and translational changes of oxygen-sensitive molecules including antioxidants. Diabetes and/or obesity ('diabesity') are associated with changes in the maternal environment, which can affect any of the distinct developmental processes ensuing modifications of onset or magnitude of oxygen tension changes. This may overwhelm the anti-oxidative defence systems developing in parallel to the physiological rise in oxygen tension. The resulting exacerbated oxidative stress, as it was demonstrated in the first trimester placentas of type 1 diabetes mellitus (T1DM) patients, may impair developmental processes. In addition, many components of the diabesity environment can have distinct molecular effects on a range of molecules, but these need to be identified. Insulin is an important contributor to early placental phenotype, because it is involved in regulation of cytotrophoblast-syncytiotrophoblast fusion and placental surface expansion. Its circulating levels are increased in T1DM, because of pharmacologic treatment, and obesity, because of beta-cell compensation of insulin resistance. This constitutes the (patho)physiological link between diabesity and placental growth changes. Microarray studies have identified several molecular and cellular candidate processes altered by insulin in obese pregnancies, including cell cycle regulation and fatty acid and cholesterol metabolism. Research on early diabesity exposure and the placenta is still in its infant stage. To stimulate further studies we have identified some important and pending questions.